AN ANALYSIS OF ADJECTIVE CLAUSES IN THE NOVEL “ANOTHER PIECE OF MY HEART” BY JANE GREEN AND ITS CONTRIBUTION TO THE TEACHING OF GRAMMAR - Ayu Nur Hidayah (Universitas Ngudi Waluyo, 2021)
Adjective clause is a dependent clause that modifies a noun. It describes, identifies or gives further information about a noun. In this case, the writer analyzes the novel named Another Piece of My Heart by Jane Green because it contains a lot of adjective clauses and gives the contribution for teaching grammar. This study aimed to find out the kinds adjective clauses in the novel, the dominant adjective clauses in the novel and the contributions of adjective clauses to the English grammar teaching. The writer used the adjective clause theory of Thomson and Martinet which defining relative pronouns used in the adjective clauses namely refer to persons, things, places, times and reason. The research design of this study was qualitative research. The writer collected all the required data from Jane Green’s novel entitled Another Piece of My Heart. The data is sentences that contain adjective clauses. There are about 413 adjective clauses found in the novel as the data sources consist of 197 adjective clauses referring to a person with percentage 47.7%. 161 adjective clauses referring to a thing with 39%, 32 adjective clauses referring to a time with percentage 7.7%, 20 adjective clauses referring to a place with 4.8%and 3 adjective clauses referring to a reason with percentage 0.8%. The adjective clauses referring to a person by using relative pronoun who is the most dominant used in the Jane Green’s novel Another Piece of My Heart with a percentage of 43.6%. The writer also takes conclusions that the result of this research can be used by the teachers in the teaching grammar. The data samples which are found in this research can be used when the teacher is delivering the lesson to the students.Keywords: Grammar, Adjective Clause, Types of Adjective Clause, Novel